Microstructure, Mechanical and Corrosion Properties of UNS 32205 Duplex Stainless Steel Weldment Joints by Multipass FCAW - Kisasoz, A.; Tumer, M.; Karaaslan, A. (WALTER DE GRUYTER GMBH, 2021)
In this study, the effect of multipass welding on the microstructure, mechanical and corrosion properties of the UNS 32205 duplex stainless steels (DSS) is investigated. The UNS 32205 DSS is welded in 3 or 7 passes by flux-cored arc welding (FCAW) using E2209 T1-1/4 flux cored wire. The weldments are characterized by light optical microscopy (LOM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Feritscope analysis, Charpy impact tests and electrochemical corrosion tests. The results suggest that the multipass FCAW process induces the formation of gamma(2 )in the weld seam. The mechanical and the corrosion properties of the weld joints are affected by the heat input variation and the phase transformations. Especially, the formation of the gamma(2) in the weld seam results in a decrease in the corrosion resistance of the joint samples.
Keywords: UNS 32205 duplex stainless steel; Flux-cored arc welding (FCAW); mechanical properties; corrosion resistance; characterization; HEAT-AFFECTED ZONE; WELDED-JOINT; INPUT; BEHAVIOR; SUPER; RESISTANCE; EVOLUTION; Metallurgy & Metallurgical Engineering